Women, Children, and Tobacco - Yuwastina, Desti (UI Scholars Hub, 2023)
Tobacco has been a well-known commodity in Indonesia, especially since kretek has attracted immense attention to be sold internationally. Both tobacco farms and tobacco industry have also been subjected to the undesirable circumstances of tobacco within the range of national and international frameworks. This research aspires to uncover the health perspective of tobacco smoking activities by underpinning the questionable way of nurturing children in the surroundings of tobacco as a way of protection towards the future of the tobacco industry. In order to unravel the novelty of the research on the subordinate roles of women and children, an enormous proportion of communication field is embodied throughout the discourse analysis, such as nonverbal communication, standpoint theory and relational schemas following the sociopsychological tradition. Overall, the paper aims to come up with the latest general overview of tobacco-related issues with different scopes of analysis in favor of the discourse on nature, nurture and culture.